GAMBARAN BUDAYA KESELAMATAN PASIEN DI RS ROEMANI MUHAMADDIYAH SEMARANG - Tio Dora Ultaria S.; Septo Pawelas Arso; Ayun Sriatmi (Jurnal Kesehatan Masyarakat (Undip), 2017)
Patient safety is the main foundation to patien safety. Patient safety culture is hospital shoud be apllied with safety system in order to decrease KTD significantly.RS Roemani Semarang has patient safety indicators in section of hospital but many are not carried out because of the low of check againts mistake made by nurses in Roemani Hospital Semarang. The purpose of the study is to see description of patient safety culture in Roemani Hospital based on 12 dimensions of patient safety culture according to AHRQ. This study uses quatitative methods and types of cross-sectional study with 72 respondents. The results of this research is description of patient safety cultureon nurse in Roemani Hospital categorized in a medium patient safety culture with percentage 71%, with detail to each dimension are dimension categorized in low culture with percentage 48,2% and 5 dimensions categorized in strong culture such us supervisor expectations promoting patient safety 84,7%, communication openness 88,9%, feedback and communication about error 88,9%, teamwork within units 86,1%, handoffs and transitions 86,1%. Dimension medium categorized are continuos improvement 72,6%, teamwork across units 71,2%, non punitive response to  error 51,8%, staffing 62,3%, management support 67,6%, overal perceptions of patient safety 74,7%. Researches suggested that the the hospitals do a root cause analysis, develop briefing, buid culture of non blaming, do declaring the patient safety a priority, and management by walking around to control and disseminate patient safety.